Key tree and Chinese remainder theorem based group key distrubution scheme - Zhou, Jie; Ou, Yong-Hao (Journal of the Chinese Institute of Engineers, 2009)
A group key distribution scheme based on static key tree structure and the Chinese Remainder Theorem (KTCRT-GKD) is proposed. It deal with the scenario of a pre-defined static prospective user set U containing all potential customs of multicast services and concentrate on the stateless receiver case. Given a privileged group member set G ⊆ U consisting of authorized users in a multicast session, a set of subtrees of the user tree whose leaves just host all the privileged group members is called group member subtrees. We design an algorithm to compute the root IDs of group member subtrees. The key server uses the root keys of the group member subtrees and the Chinese Remainder Theorem to distribute a group key. It can reduce the key server's computation complexity for each group key distribution. Especially, an interesting feature is that, when the number of group members exceeds a certain number, the computing time of the key server will decrease with the increase of the size of the group.